Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2023)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2023)

Charting the Course : 2022-2023 Year in Review - Youth for Youth Québec (Y4Y Québec) (2023)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2023)

Community Connections : Youth Perspectives on Mental Health - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

Newsletter - Youth for Youth Québec (Y4Y Québec) (2022)

A 5-Year Strategic Plan to Help Guarantee the Ongoing Vitality of Quebec’s English-speaking Youth : 2022-2027 - Youth for Youth Québec (Y4Y Québec) (2022)
The Plan is meant to articulate the needs, the issues, and the priorities of Québec’s English-speaking youth community (ages 16 – 30) It is a living document that will be reviewed and adapted over the 5-year span to reflect the changing needs within the community and the world.

Annex : A 5-Year Strategic Plan to Help Guarantee the Ongoing Vitality of Quebec’s English-speaking Youth : 2022-2027 - Youth for Youth Québec (Y4Y Québec) (2022)

Evaluation Report - Holley, Paul (Youth for Youth Québec (Y4Y Québec), 2020)
The following evaluation report fulfills a key deliverable of a broader project funded by Canadian Heritage and titled Best Practices in Community Engagement for the English Speaking Youth Population in Quebec, which was implemented by Youth 4 Youth (Y4Y) Quebec from April 1, 2019 to March 31, 2020. The key objective of this project was to boost youth engagement and participation in political and community life in Quebec. Y4Y successfully accomplished this objective by engaging over 1,000 youth through a series of 30 community consultations, 12 focus groups, and a youth survey delivered on-line and in-person with 520 respondents. The focus of this report is on the key findings from the survey, which targeted Englishspeaking youth ages 16 to 30 from across the province and collected quantitative and qualitative information on youth media consumption and community engagement activities. A gender-based analysis of key survey findings was also conducted and is presented in this report along with a set of recommendations for community organizations serving Quebec’s English-speaking youth population.

Y4Y Quebec Congratulates Executive Committee Member Hayley Campbell for Winning the 2018 Young Quebecers Leading the Way Award - Youth for Youth Québec (Y4Y Québec) (2018)

Recommendations to Address Community Disengagement Amongst Quebec's English-speaking Youth Population - Youth for Youth Québec (Y4Y Québec)